Direct and indirect urban water footprints of the United States. Issue 1 (13th January 2017) - Chini, Christopher M.; Konar, Megan; Stillwell, Ashlynn S.
Abstract: The water footprint of the urban environment is not limited to direct water consumption (i.e., municipal supplies); embedded water in imported resources, or virtual water transfers, provides an additional component of the urban water footprint. Using empirical data, our analysis extends traditional urban water footprinting analysis to quantify both direct and indirect urban resources for the United States. We determine direct water volumes and their embedded energy through open records requests of water utilities. The indirect component of the urban water footprint includes water indirectly consumed through energy and food, relating to the food‐energy‐water nexus. We comprehensively quantify the indirect water footprint for 74 metropolitan statistical areas through the combination of various databases, including the Commodity Flow Survey of the U.S. Census Bureau, the U.S. Department of Agriculture, the Water Footprint Network, and the Energy Information Administration. We then analyze spatial heterogeneity in both direct and indirect water footprints, determining the average urban water footprint in the United States to be 1.64 million gallons of water per person per year [6200 m 3 /person/yr or 17, 000 L/person/d], dominated by indirect water. Additionally, our study of the urban water cycle extends beyond considering only water resources to include embedded energy and equivalent carbon dioxide emissions. The inclusion of multiple sectors of the urban water cycle and their underlying processes provides important insights to the overall urban environment, the interdependencies of the food‐energy‐water nexus, and water resource sustainability. Our results provide opportunities for benchmarking the urban energy‐water nexus, water footprints, and climate change potential. Key Points: The total urban water footprint includes direct and indirect water inputs and opportunities for energy and water benchmarking Conservation opportunities exist for water and energy in direct and indirect water resources Water embedded in food resources dominates the total urban water footprint